Determining the optimal timing for Tetralogy of Fallot management: A meta-analysis of neonatal vs postneonatal repairs - Starry Homenta Rampengan; Stevanus Christian Surya; Derren David Christian Homenta Rampengan; Sebastian Emmanuel Willyanto; Roy Novri Ramadhan; Bryan Gervais de Liyis; Alif Hakim Alamsyah; Melissa Valentina Ariyanto; Muhammad Iqhrammullah (Annals of Pediatric Cardiology)
Background: Tetralogy of Fallot (TOF), the most prevalent cyanotic congenital heart anomaly, impacts around 3.9 in 10,000 live births. Repair aims to address intracardiac shunting and right ventricular outflow tract obstruction. Despite successful historical surgeries, the optimal timing for repair remains debated. Objective: The aim of the study was to provide an updated comparison of the TOF repair timing (neonatal vs. postneonatal periods) based on post- and perioperative outcomes. Methods: A literature search was conducted across PubMed, Scopus, EBSCO, Science Direct, and Epistemonikos. Quality assessment was performed using the Risk of Bias in Non-Randomized Studies of Interventions, whereas the outcomes were analyzed using RevMan 5.4. Results: Nineteen studies comprising 28,968 patients were included in the study. All studies were classified as high-quality. The neonatal repair exhibited longer intensive care unit (ICU) stays (standard mean differences [SMD] 1.58; 95% confidence interval [CI] 1.04–2.12; P < 0.00001) and hospital stays (SMD 5.18; 95% CI 3.54–6.82; P < 0.00001). Moreover, the analysis showed an overall result favoring the postneonatal repair, including mortality (odds ratio [OR] 1.68; 95% CI 1.47–1.92; P < 0.00001), delayed chest closure (OR 2.52; 95% CI 2.06–3.09; P < 0.00001), and pacemaker implantation (OR 3.68; 95% CI 2.89–4.70; P < 0.00001). Conclusion: Complete repair during the post-neonatal period yielded better postoperative outcomes, shorter hospital stays, ICU stays, and ventilation time. PROSPERO registration: CRD42024503630.